Dilema Pemerintah: Menghadapi Wabah Covid-19 Butuh Dana, Tapi Memungut Pajak Menjadi Tak Bijaksana - Putriana Salman; Noor Safrina (Jurnal Ilmu Ekonomi dan Bisnis, 2021)
The purpose of this research to explain that the efforts made by the government in the taxation sector in dealing with the Covid-19 pandemic are to provide tax relaxation to the business world. The research method used is literature study, by selecting the type of descriptive research. The results of this study would like to suggest that during the COVID-19 pandemic, the people needed government assistance for their survival. Therefore, the role of the government and the policies taken to tackle COVID-19 are urgently needed, especially the provision of assistance to the community that comes from taxes, even though this is a